2022
DOI: 10.1371/journal.pone.0270529
|View full text |Cite
|
Sign up to set email alerts
|

Constructivist multi-criteria model to support the management of occupational accident risks in civil construction industry

Abstract: Civil construction is one of the industrial sectors with continuous growth globally, particularly in Brazil in the last 50 years. Unfortunately, it is also one of the productive segments with the highest incidence of accidents, which overshadows its merits as a driver of economic growth and job creation. The damage to workers’ health caused by accidents at work results from the presence of work environment risk factors. Therefore, this study aims to manage these risk factors for the civil construction industry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 51 publications
(168 reference statements)
0
3
0
5
Order By: Relevance
“…In risk management field 25 out of 61 papers dealt with data on the "risk management process". Into this class the 54 observations out of 202 concerned the following topics: awkward working postures [7,19]; compliance with Health and Safety standards [2,4,47]; risk assessment [21,51,53,63,66,77,79]; safe climate [44]; slope instability [10,17]; teaching-training tasks [5,6,78]; unsafe behaviours [25,72]; worker fatigue-heat stress [38,69,73]; site image [1,46]. Antwi-Afari et al [7] used deep learning networks to automatically extract relevant features with spatial-temporal dependence acquired by a wearable insole pressure system.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…In risk management field 25 out of 61 papers dealt with data on the "risk management process". Into this class the 54 observations out of 202 concerned the following topics: awkward working postures [7,19]; compliance with Health and Safety standards [2,4,47]; risk assessment [21,51,53,63,66,77,79]; safe climate [44]; slope instability [10,17]; teaching-training tasks [5,6,78]; unsafe behaviours [25,72]; worker fatigue-heat stress [38,69,73]; site image [1,46]. Antwi-Afari et al [7] used deep learning networks to automatically extract relevant features with spatial-temporal dependence acquired by a wearable insole pressure system.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…In the next stage, the Construction of the Family of Points of View, there is a more effective participation of the decision maker, which allows to build the criteria that best align with its values (Bortoluzzi et al, 2010). Semi-structured interviews are conducted, with the elaboration of open questions adapted to the context, seeking that the decision maker identify the concerns that directly or indirectly influence the research focus problem (Ensslin et al, 2022). Through these interviews, it is possible to identify the Primary Evaluation Elements (EPAS), being characteristics or properties of the context of what the decision maker thinks impact their values (Bortoluzzi et al, 2010).…”
Section: Structuring Phasementioning
confidence: 99%
“…A constructivist multi-criteria model analysis was utilised to create a model to support the management of the risk of accidents on construction sites by Ensslin et al [114]. The study identified strategic objectives and examined the criteria scales, including performance profiles, and proposed vulnerability improvement activities.…”
Section: Ohsms Awareness and Model-related Analysismentioning
confidence: 99%